Differential Responses by Human Macrophages to Infection With Mycobacterium tuberculosis and Non-tuberculous Mycobacteria - Feng, Zhihong; Bai, Xiyuan; Wang, Tao; Garcia, Cindy; Bai, An; Li, Li; Honda, Jennifer R.; Nie, Xiuhong; Chan, Edward D. (Frontiers in Microbiology, 2020)
Mycobacterium tuberculosis (MTB) and non-tuberculous mycobacteria (NTM) are formidable causes of lung diseases throughout the world. While MTB is considered to be more virulent than NTM, host factors also play a key role in disease development. To elucidate whether there are differential immune responses to various mycobacteria, THP-1 macrophages were temporally infected with MTB H37Rv or with four different NTM species. We found that cells infected with MTB had greater bacterial burden and p65 NFκB activation than cells infected with NTM. There was also differential expression of mRNA for interleukin-1- (IL-1β, IL-8, IL-10, and tumor necrosis factor-alpha (TNFα) with no distinct pattern of mRNA expression among the different mycobacteria. In contrast, at the protein level, some generalizations can be made of the cytokines and chemokines expressed. Compared to uninfected cells, the rapid-growing Mycobacterium smegmatis but not Mycobacterium abscessus induced significantly greater pro-inflammatory cytokines and IL-10, whereas both NTM individually induced greater levels of chemokines. Compared to uninfected control cells, the two slow-growing NTM and MTB differentially induced cytokine expression with Mycobacterium avium inducing more pro-inflammatory cytokines and IL-10, whereas M. avium, Mycobacterium intracellulare, and MTB inducing greater but similar levels of chemokines. MTB-infected THP-1 cells also demonstrated lower level of phagosome-lysosome fusion and apoptosis than NTM-infected cells while there were differences in these macrophage functions among the NTM species. Interestingly, M. intracellulare, M. avium, and MTB have similar levels of autophagosome formation, but the levels displayed by all three were lower than for M. smegmatis and M. abscessus. This study demonstrates the differences in bacterial burden and macrophage effector functions among several clinically relevant mycobacterial species. Such disparities may, in part, account for differences in clinical outcomes among patients infected with various species of NTM as has been seen for different strains of MTB.